The moderating role of perceived social support on the relationship between shift work and individual appraisal toward employee engagement among hotel employees - Murti, Nino Ranu Hari (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
This study aims to examine the effect of irregular shift work on hotel employee engagement, taking into account the role of perceived individual hindrances and perceived social support. A quantitative approach was employed, involving 162 hotel employees in Surabaya who work under a shift-based operational system. Data were collected through structured questionnaires and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results indicate that irregular shift work significantly increases the perception of individual hindrances, which in turn negatively affects employee engagement. Furthermore, perceived social support acts as a moderator in two key relationships. First, social support weakens the positive effect of irregular shift work on perceived hindrances, meaning that employees who receive social support are less likely to view shift work as a hindrance. Second, social support also reduces the negative relationship between perceived hindrances and engagement, enabling employees to maintain their engagement despite facing work-related obstacles. These findings highlight the importance of managing the work environment not only from an operational standpoint but also from social and psychological perspectives. The study offers a theoretical contribution by testing a dual moderation model in the hospitality industry context, integrating the transactional stress theory and the job demands-resources framework.